Presence of Senescent and Memory CD8+ Leukocytes as Immunocenescence Markers in Skin Lesions of Elderly Leprosy Patients - da Silva, Pedro Henrique Lopes; de Castro, Katherine Kelda Gomes; Mendes, Mayara Abud; Leal-Calvo, Thyago; Leal, Júlia Monteiro Pereira; Nery, José Augusto da Costa; Sarno, Euzenir Nunes; Lourenço, Roberto Alves; Moraes, Milton Ozório; Lara, Flávio Alves; Esquenazi, Danuza (Frontiers in Immunology, 2021)
Leprosy is an infectious disease that remains endemic in approximately 100 developing countries, where about 200 thousand new cases are diagnosed each year. Moreover, multibacillary leprosy, precisely the most contagious form of the disease, has been detected at continuously higher rates among Brazilian elderly people. Due to the so-called immunosenescence, characterized by several alterations in the quality of the immune response during aging, this group is more susceptible to infectious diseases. In view of such data, the purpose of our work was to investigate if age-related alterations in the immune response could influence the pathogenesis of leprosy. For such, we studied 87 individuals, being 62 newly diagnosed and untreated leprosy patients distributed according to the age range and to the clinical forms of the disease. Additionally, 25 healthy volunteers were studied as controls. The frequency of cytotoxic and memory CD8+ T lymphocytes was assessed by immunofluorescence of biopsy from cutaneous lesions, while the serum levels of IgG anti-CMV antibodies were analyzed by chemiluminescence and the gene expression of T cell receptors’ inhibitors by Real Time RT-qPCR. We noted an accumulation of memory CD8+ T lymphocytes, as well as a reduced CD8+CD28+ T cell expression of skin lesions from elderly patients, when compared to younger. Alterations in the LAG3 and PDCD1 gene expression in cutaneous lesions of young MB patients were also observed, when compared to elderly. Such data suggest that the age-related alterations of T lymphocyte subsets can facilitate the onset of leprosy in elderly, not to mention other chronic inflammatory diseases.